LODGING OF SUGARCANE IN STRONG WINDS - VENKITESHWARAN , S.P.; SRINIVASAN, P.S. (MAUSAM, 1955)
Lodging of sugarcane can occur due to its being blown down by wind, particularly after the cane has completed elongation.